MANAGEMENT PERSONNEL RECRUITMENT EDUCATION RESOURCES (Entrepreneur, 2012)
Abstract Employees or personnel, especially teachers are the spearhead in the process of Islamic education Islamic education process will not work properly without the teachers role. Institutionally, the progress of a further education institution is determined by the leadership of these institu tions than others,but in the learning process the teacher plays the most decisive than the method or material. The role of teachers in the learning process is depicted in Arabic phrase has ever delivered A. Malik Fadjar.